Parent's use of strategies to monitor children's activities online - Maserumule, Ngwanadira Tebogo (My University, 2017)
Although studies have been conducted on the effectiveness of different types of filtering software, limited knowledge is available on parents’ use of strategies to monitor their children’s activities online. Thus, identifying understanding parents’ use of strategies to monitor children’s activities online and the extent in which parents use content filtering software will contribute to the body of knowledge. The purpose of this study is to understand parent’s use of strategies to monitor children’s activities online and the extent in which they use content filtering software in Gauteng Province, South Africa. The study adopted a Social Cognitive Theory to develop a conceptual framework and identify existing theoretical concepts. The conceptual framework adapted Bandura’s (2001) framework to inform data analysis. Data were collected through semi-structured interviews and qualitative, thematic content analysis was used for data analyses. The results of the study indicated that parents do use various strategies to monitor children’s activities online and further apply knowledge, experience, and social support as a rationale for using those strategies. The study further revealed that there is a gap between parents, technology industry and government regarding the use of content filtering software. Thus, the study recommends parents, industry and government work together to protecting children online through various strategies and address the concerns regarding the use of content filtering software. Parents’ need to understand the importance of content filtering software and discuss this with their children to be able to protect them online without restricting access to relevant information. Keywords: Harmful content, blocking, strategies, filtering, online content, software, use, non-use, strategies
Thesis (M.Com. (Information Systems))--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Economic and Business Sciences, 2017
Keywords: Computers--Access control; Internet and children; Internet--Security measures; Internet--Censorship